Amphioxus neuroglia: Molecular characterization and evidence for early compartmentalization of the developing nerve cord. Issue 7 (24th February 2021) - Bozzo, Matteo; Lacalli, Thurston C.; Obino, Valentina; Caicci, Federico; Marcenaro, Emanuela; Bachetti, Tiziana; Manni, Lucia; Pestarino, Mario; Schubert, Michael; Candiani, Simona
Abstract: Glial cells play important roles in the development and homeostasis of metazoan nervous systems. However, while their involvement in the development and function in the central nervous system (CNS) of vertebrates is increasingly well understood, much less is known about invertebrate glia and the evolutionary history of glial cells more generally. An investigation into amphioxus glia is therefore timely, as this organism is the best living proxy for the last common ancestor of all chordates, and hence provides a window into the role of glial cell development and function at the transition of invertebrates and vertebrates. We report here our findings on amphioxus glia as characterized by molecular probes correlated with anatomical data at the transmission electron microscopy (TEM) level. The results show that amphioxus glial lineages express genes typical of vertebrate astroglia and radial glia, and that they segregate early in development, forming what appears to be a spatially separate cell proliferation zone positioned laterally, between the dorsal and ventral zones of neural cell proliferation. Our study provides strong evidence for the presence of vertebrate‐type glial cells in amphioxus, while highlighting the role played by segregated progenitor cell pools in CNS development. There are implications also for our understanding of glial cells in a broader evolutionary context, and insights into patterns of precursor cell deployment in the chordate nerve cord. Main Points: Amphioxus has astroglia‐ and radial glia‐like cells. Neurons and glia arise from different precursor populations. Multipotent radial glia‐like progenitors were likely present in the last common ancestor of deuterostomes.